y=x-2? just instead of x put the numbers => y=-2-2 => y=-4 etc.
2007-01-19 03:53:25
·
answer #1
·
answered by deana m 3
·
0⤊
0⤋
Replace x with the given values to compute y (I am assuming the formula is 1/(x-2):
when:
x = -2; y = 1/(-2-2) = -1/4
x = -1, y = 1/(-1-2)) = -1/3
x = 0, y = 1/(0-2) = -1/2
x = 1, y = 1/(1-2) = -1
x = 2, y = 1/(2-2) = 1/0 = imaginary (undefined)
x = 3, y = 1/(3-2) = 1
2007-01-19 04:04:06
·
answer #2
·
answered by dirkjohn69 4
·
0⤊
0⤋
I assume you mean: 1/(x-2) correct?
First: replace each value/number with the x-variable in the expression...
a. x = - 2
1/(-2-2)
1/-4
= -1/4
b. x = - 1
1/(-1-2)
1/-3
= -1/3
c. x = 0
1/(0-2)
1/-2
= -1/2
d. x = 1
1/(1-2)
1/-1
= -1
e. x = 2
1/(2-2)
1/0
= undefined
f. x = 3
1/(3-2)
1/1
= 1
2007-01-19 04:12:41
·
answer #3
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
you must put these numbers instead x
x=-2 y= -1/4
x=-1 y=-1/3
x=0 y=-1/2
x=1 y= -1
x=2 y doesn´t exist because the denominator becomes 0 and you can´t divide by zero
x=3 y=1
2007-01-19 03:59:43
·
answer #4
·
answered by santmann2002 7
·
0⤊
0⤋
for x=-2, y= 1/(-2-2) y=-1/4
for x=-1, y=1/(-1-2) y=-1/3
for x=0, y=1/(0-2) y=-1/2
for x=1, y=1/(1-2) y=-1
for x=2, y=1/(2-2) y doesnt exist you cant divide by zero
for x=3, y=1/(3-2) y=1
hope that helps
2007-01-19 04:03:21
·
answer #5
·
answered by zs8nt 2
·
0⤊
0⤋
To get 1/(x-2), simply subtract 2 from x, and take its reciprocal (where the reciprocal of y is 1/y, or the solution z to zy=1, such as 1/2 is the reciprocal of 2), where defined. You don't need our help.
2007-01-19 03:54:39
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
x=mp
2007-01-19 03:51:38
·
answer #7
·
answered by john t 4
·
0⤊
1⤋
what is _1_ supposed to mean?
2007-01-19 03:53:58
·
answer #8
·
answered by Anonymous
·
1⤊
0⤋